(untitled) (REMUNOM, 2025)
This article analyzes the limits to resocialization in the Brazilian socio-educational system and its relationship with the high rates of recidivism among adolescents in conflict with the law. Despite the existence of an advanced legal framework, consolidated by the Child and Adolescent Statute (ECA) and the National Socio-educational Assistance System (SINASE), structural, institutional and social flaws persist that compromise the effectiveness of socio-educational measures. The research, of a qualitative nature, is based on a bibliographic and documentary review, in addition to the analysis of data from institutions such as CNJ, IPEA and the Brazilian Public Security Forum. It is concluded that recidivism is directly associated with the insufficiency of integrated public policies, the inadequate conditions of socio-educational units and the persistence of a punitive culture, revealing the distance between current regulations and institutional practice. The study demonstrates the urgent need to reformulate socio-educational policies, focusing on comprehensive protection, social inclusion and prevention of recidivism.